The role of Logistics Management Information System (LMIS) in the health commodity supply chain management in Bangladesh at lower health care level(community based clinic and upazilla hospital) - Hakim, Md Abdul (Brac University, 2024)
This practicum report is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2020.